Mereka Kerdil: Diskursus Elite Politik di Media Alternatif - Wahid, Abdul (Universitas Brawijaya, 2024)
A reliance on official sources and a tendency to reinforce established narratives characterize mainstream media representations of political elites. This study seeks to analyze how Sediksi, as an alternative media, interprets political elites. Through critical discourse analysis, it examines how hegemony and inequality are reproduced through language, especially from the perspective of marginalized groups. This study shows that alternative media provides a critical lens that challenges dominant elite representations. By using satirical language, alternative media interpret elites as dwarfed by various associations with incompetence, ignorance, corruption, deceit, and marginalized communities. Alternative media not only provides space for criticism of political elites, but also empowers the public to challenge the narratives imposed by dominant forces. By amplifying marginalized voices, alternative media encourages collective resistance and builds public awareness by presenting issues that people often face in their daily lives. This study argues that alternative media is capable of creating more inclusive interpretations and siding with marginalized perspectives.